2006
DOI: 10.1124/mol.106.026120
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Structure-Based Alignment of Prokaryotic and Eukaryotic Neurotransmitter/Na+Symporters (NSS) Aids in the Use of the LeuT Structure to Probe NSS Structure and Function

Abstract: The recently elucidated crystal structure of a prokaryotic member of the neurotransmitter/sodium symporter (NSS) family (Yamashita et al., 2005) is a major advance toward understanding structure-function relationships in this important class of transporters. To aid in the generalization of these results, we present here a comprehensive sequence alignment of all known prokaryotic and eukaryotic NSS proteins, based on the crystal structure of the leucine transporter from Aquifex aeolicus (LeuT). Regions of low s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
364
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(376 citation statements)
references
References 48 publications
12
364
0
Order By: Relevance
“…In LeuT Aa , TMs 1, 3, 6, and 8 form the leucine binding pocket. Biochemical analyses and homology modeling of SERT proteins predict a similar binding pocket for 5-HT (32)(33)(34)(35)(36). Consistent with these models, pre-structure studies identified residues in hSERT TMs 1 and 3 that confer high affinity interactions and ligand selectivity to substrates and antagonists.…”
supporting
confidence: 49%
See 2 more Smart Citations
“…In LeuT Aa , TMs 1, 3, 6, and 8 form the leucine binding pocket. Biochemical analyses and homology modeling of SERT proteins predict a similar binding pocket for 5-HT (32)(33)(34)(35)(36). Consistent with these models, pre-structure studies identified residues in hSERT TMs 1 and 3 that confer high affinity interactions and ligand selectivity to substrates and antagonists.…”
supporting
confidence: 49%
“…Impact of Na ϩ on MTSET Inactivation-The LeuT Aa crystal structure and hSERT homology models derived from it predict that TM6 is involved in the coordination of a sodium ion (27,(32)(33)(34)36). Interestingly, replacement of sodium with NMDG in the MTS incubation buffer resulted in protection of three TM6 Cys mutants and exposure of a single mutant (Fig.…”
Section: G338c Appears To Stabilize An Open Conformation Of Hsert-mentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemistry with a GAT antibody confirmed that all of the mutant proteins localized to the membrane similarly to the wild-type protein (data not shown). Finally, the location of the binding site is in agreement with those of the other GATs (20,53). For example, the mouse GAT-3 (i.e., GAT-4) binding site is almost identical to that of our GAT-2 model (54).…”
Section: Mode Of Gat-2 Interaction With Gaba-supporting
confidence: 69%
“…The crystal structure of LeuT (9) provides an example of a structure where the binding site is exposed to only one side of the membrane, in this case to the extracellular surface. LeuT has provided a useful structural model for members of the neurotransmitter sodium symporter (NSS) family (9,15). These proteins include transporters mediating the reuptake of neurotransmitters and amino acids.…”
mentioning
confidence: 99%